Gestão da cadeia de suprimentos de serviços e big data analytics: a influência na satisfação do cliente - Silva, Douglas Vieira da (2019)
Services have been present in people's life daily, providing, daily contacts with companies services in a wide range of segments such as food, transport, communication, health, safety, residential and residential condominiums. The diversity of services is often found in one place. In this context, this study addressed the constructs "Service Management (SM)", "Management of Logistic Services (MLS)", "Service Supply Chain Management (SSCM)", "Big Data Analytics (BDA) Operational Performance (OP) "and" Customer Satisfaction (CS) ", aiming to analyze the mediating effect of Big Data Analytics on Operational Performance and, consequently, Customer Satisfaction. The research site was the residential condominiums of the São Paulo area. For this, a research composed of two phases was carried out. The first, of a qualitative exploratory nature, through in-depth interviews with three condominiums and their respective service providers. On the one hand, the subjects of the first phase were the syndics, condominium managers and janitors, and on the other hand, service providers (elevators, security, maintenance). The data collected from this phase were treated by content analysis. With the results of the exploratory research, the second phase was carried out, being this one, of a descriptive nature of the quantitative type. At the moment, a questionnaire was developed and applied to a total of 125 respondents, chosen for accessibility, with the same profile as the subjects of the research carried out in the first phase. In both phases, the companies participating in the present study are utilitarian of at least two of the dimensions of the BDA. The data collected at this stage were treated by descriptive statistics (to examine the outliers data) and by modeling in structural equations. The data presented revealed that the BDA is an important management tool, having positive consequences in the SSCM, in the OP and, consequently, in CS. The extent to which service providers understand such a relationship, and are willing to use BDA as a facilitating tool for processes such as storage, distribution, service execution, aftersales, among others, can thus better develop and satisfy their customers better delivery times and conditions, improvement of the quality of the services performed and the relationship between the customer and the supplier. Finally, from the relations established between the presented variables, it was possible to verify that the BDA has a mediating effect on the relationship between SSCM and the OP.